Antibacterial, antibiofilm, hemolytic activity and phytochemical study of various aerial parts of Moringa oleifera in Pakistan - Dilawar, Shahnaz; Shah, Afzal; Khan, Hidayat Ullah; Imad, Saima (Asian Journal of Medical and Biological Research, 2018)
Theamethanolicoextractsaofffiveeaerial parts ofaMoringa oleifera Lamwwereascreened for their antibacterial, antibiofilm and hemolytic activity.”Theaphytochemical screening of the methanolic extracts of aerial parts was also evaluated. The antibacterial, antibiofilmiactivityiof the extractssof various aerial parts of M. oleifera was evaluated by disc diffusion and micro titer plate assay method against two selected bacterial species. Hemolyticaactivity of the methanoliciextracts was screened against normal human erythrocytes. Comparatively the methanolic extracts of all aerial parts were more effective against Gram positive bacteria Bacillus subtilis and Gram negative bacteria Escherichia coli (E. coli) .The present study suggests that all aerial parts of this plant can be used as an antibacterial, anti-biofilm agent in treating ailments caused by the tested organisms (Bacillus subtilis and Escherichia coli). Methanolic extracts of aerial parts possessed minimum hemolytic activity. Significant antimicrobial, antibiofilm activity of the extract was found in this study. Asian J. Med. Biol. Res. March 2018, 4(1): 77-85